Alaska subsistence : a National Park Service management history - Norris, Frank B. (Frank Blaine), 1950-; United States. National Park Service. Alaska System Support Office. ([Anchorage, Alaska] : Alaska Support Office, National Park Service, 2002)
"September 2002." Includes bibliographical references and index. Alaska Native and rural lifeways prior to 1971 -- National Park Service and the subsistence question -- Subsistence in Alaska's parks, 1910-1971 -- Alaska lands question, 1971-1980 -- Initial subsistence management efforts -- Managing Alaska's subsistence program, 1985-1989 -- Federal assumption process, 1989-1993 -- NPS subsistence management activities, 1990-present -- Subsistence fishing question. Mode of access: Internet.